+0  
 
0
76
1
avatar

Let \( f(x) =\frac {3x^2 + 5x + 8} {x^2 - x + 4 }\) and \(g(x) = x - 1. \) Find \(f(g(x)), \) evaluated when \( x = 1.\)

Guest Feb 21, 2018
 #1
avatar+87333 
+1

f(g(x) = 

 

[ 3 (x - 1)^2 + 5(x - 1) + 8 ] / [ ( x - 1)^2 - (x - 1) + 4 ]

 

So

 

f(g(1) )  =

 

[ 3 (1 - 1)^2 + 5(1 - 1) + 8 ]  / [ (1 - 1)^2 - (1 - 1)  + 4 ] =

 

[ 3 (0)^2  + 5(0) + 8 ] /  [ (0^2  - 0  + 4 ]  =

 ]  / [ 0 - 0 + 4 ] =

 

8 / 4    =   2

 

 

cool cool cool

CPhill  Feb 21, 2018

1 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.